DENTAL AGE ASSESSMENT OF PAKISTANI CHILDREN USING DEMIRIJIAN METHOD - Muhammad Ishaque; Arslan ali Vistro; Shazia Parveen Rajpar; Priya; Sadia Rizwan; Taskeen Khan (Pakistan Oral & Dental Journal, 2020)
The study was done to evaluate the accuracy of Demirijian Method when used for age determination in Pakistani children. A retrospective study was carried out at the department of orthodontics. Forty patients of 8.5-17 years of age having normal morphology of teeth and willing to participate were included in the study and patients with missing teeth (extracted or naturally missing) or having any medical disorder were excluded. The mandibular left quadrant excluding 3rd molars was assessed. Central incisor to second premolar teeth were examined in OPG and a separate score was given to each tooth according to the stage of its development seen from the available tables. The mean dental age ± SD evaluated by using Demirjian’s method for the boys was 11.97± 2.38(8.5 to 16 years) whereas for the girls was 12.78 ± 2.64 (9 to 17 years).Dental age measured using Demirjian’s technique for the female subjects was significantly over-estimated in the 9 year and 13–17 year age groups. It was concluded from the results of this study that Demirijian Method resulted in over-estimation of age when compared to chronological age of the subjects.